2020
DOI: 10.14324/111.444.ijsp.2020.v9.x.001
|View full text |Cite
|
Sign up to set email alerts
|

In search of a social pedagogical profession in schools. Missions and roles under reconsideration

Abstract: School is one of the areas where social pedagogy has taken on an increasingly important function. Supported by available literature, the aim of this literature review is to describe and analyse how the work of social pedagogues in schools can be manifested. The literature review shows that social pedagogical work in schools is common in many countries and emerging in others. The study shows a wide variation both between and within countries with regard to the mission and goals, status, role and function, tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Ultimately, democratising Lou's class was about more than his actions as a social pedagogue to state an explicit intention, repeat invitations to collaboration or encourage through time and space to foster collaboration. It required unlearning expected roles and instantiated hierarchies in higher education (Anderberg, 2020). Similar to what Eichsteller and Holthoff (2012) found in their study of an implementation of social pedagogy in a children's home in Essex, we also found that unlearning and trust were developed through ongoing dialogue, trusting relationship and the development of a new culture.…”
Section: Remaking Space Requires Unlearningsupporting
confidence: 84%
See 2 more Smart Citations
“…Ultimately, democratising Lou's class was about more than his actions as a social pedagogue to state an explicit intention, repeat invitations to collaboration or encourage through time and space to foster collaboration. It required unlearning expected roles and instantiated hierarchies in higher education (Anderberg, 2020). Similar to what Eichsteller and Holthoff (2012) found in their study of an implementation of social pedagogy in a children's home in Essex, we also found that unlearning and trust were developed through ongoing dialogue, trusting relationship and the development of a new culture.…”
Section: Remaking Space Requires Unlearningsupporting
confidence: 84%
“…We also aim to demonstrate how explorations of democratic education in the USA enter into extant conversations about social pedagogy and critical social pedagogy in Europe (for example, Anderberg, 2020;Kalagiakos, 2015;Kyriacou, 2009;Matikainen et al, 2018). We present three findings that speak to the necessarily messy work of unlearning institutionalised norms that sustain hierarchical teaching and learning relationships and demonstrate the nature of a maieutic 2 disposition in bringing to life more democratic conceptions of teaching and learning.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The problem of Culture (pp. [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] Cultures vary across many different dimensions. Weeks (2022[83]) points to Schein and Schein's (2017 [98]) 16 considerations for cultural challenges in cross-sector collaborations.…”
Section: Box 52 Community Schools On the Rise In The United Statesmentioning
confidence: 99%
“…To summarize, according to Anderberg (2020) the review shows the global differences as it comes to the role of social pedagogues in schools (about their missions, goals, status, roles, functions, tasks, activities). The central mission in most countries is to fight the exclusion of pupil groups or individuals with problems.…”
Section: Social Pedagogy's Connection To Practicementioning
confidence: 99%